2015
DOI: 10.1038/ismej.2015.25
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen loss by anaerobic oxidation of ammonium in rice rhizosphere

Abstract: Anaerobic oxidation of ammonium (anammox) is recognized as an important process for nitrogen (N) cycling, yet its role in agricultural ecosystems, which are intensively fertilized, remains unclear. In this study, we investigated the presence, activity, functional gene abundance and role of anammox bacteria in rhizosphere and non-rhizosphere paddy soils using catalyzed reporter deposition–fluorescence in situ hybridization, isotope-tracing technique, quantitative PCR assay and 16S rRNA gene clone libraries. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 48 publications
4
46
0
Order By: Relevance
“…NH 3 volatilization was estimated as 1.4% of fertilized N [30]. Recently, some reports have pointed out the possibilities that anaerobic oxidation of ammonium (anammox) can be a significant process of nitrogen dynamics in a flooded paddy soil [31][32][33]. However, N 2 emission via anammox from rice paddy was not considered in this study due to their limitation in quantitative evaluation.…”
Section: Other Flowsmentioning
confidence: 99%
See 1 more Smart Citation
“…NH 3 volatilization was estimated as 1.4% of fertilized N [30]. Recently, some reports have pointed out the possibilities that anaerobic oxidation of ammonium (anammox) can be a significant process of nitrogen dynamics in a flooded paddy soil [31][32][33]. However, N 2 emission via anammox from rice paddy was not considered in this study due to their limitation in quantitative evaluation.…”
Section: Other Flowsmentioning
confidence: 99%
“…The N loss in this study was higher than reported previously (e.g., +1.28 g N m −2 in [11], +0.4 g N m −2 in [10]). As described above, uptake of soil nitrogen by rice in paddy fields converted from upland fields could be larger than those in unconverted paddies [31,32]. To avoid over-luxuriant growth and lodging due to the increased nitrogen uptake, nitrogen fertilization to paddy fields converted from upland fields is limited.…”
Section: Nitrogen Budgetmentioning
confidence: 99%
“…Heterotrophic denitrification was considered to be the only known pathway for the loss of fixed nitrogen to the atmosphere for decades until the discovery of anammox bacteria in a wastewater treatment plant (Mulder et al 1995). Subsequently, anammox bacteria were detected with broad biogeographic distribution in various natural ecosystems, including marine sediments (Thamdrup and Dalsgaard 2002;Trimmer and Nicholls 2009;Brabandere et al 2014;Shao et al 2014;Dang et al 2016), estuarine sediments (Dale et al 2009;Dang et al 2010;Li et al 2011;Wang et al 2012a, b;Dang et al 2013), and paddy soils (Zhu et al 2011;Nie et al 2015;Yang et al 2015). The relative contribution of anammox to dinitrogen production can vary widely, with >80% of total N 2 production observed in the eastern tropical South Pacific oxygen minimum zone (OMZ) off the coast of northern Chile (Brabandere et al 2014).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…These reports provide insight into the biological N cycle. The anammox process has been investigated in various natural and artificial habitats (24,25).…”
mentioning
confidence: 99%